Theological Study of The Doctrine of The Trinity of God - Waruwu, Sabarani; Terasa Duha; Dapot Damanik; Elisamark Sitopu (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The Doctrine of the Trinity is teachings central in Christian theology states that Lord is one, but consists of from three personal: Father, Son (Jesus Christ), and the Holy Spirit. Although the term " Trinity " is not appear in a way direct in Bible, concept This expressed through various verses that show unity and relationship between third personal such as​ in Matthew 28:19 and 2 Corinthians 13:13. This study aiming for to study in a way deep origin proposal, development and understanding theological about doctrine Trinity, and challenges faced​ in its acceptance among Christians. Method research used​ is descriptive qualitative, which focuses on understanding meaning and experience individual related doctrine This. Research this also includes analysis history shows​ How teachings Trinity has become subjects included​ in circles theologian since 2nd and 3rd centuries AD, with contribution significant from figures like Tertullian and Athanasius. Although there is various interpretation and controversy, proper understanding​ about Trinity considered important for life Christian faith. Conclusion of study This confirm that doctrine Trinity No only is draft theological, but also has meaning practical for life daily Christians. With understand connection between Father, Son, and Holy Spirit, Christians are invited for life in love and unity, reflecting the character of God in interaction they with fellow. Research This emphasize importance delve deeper doctrine Trinity as runway strong faith​ for Christians around the world.